Adapting the Adapted: The Black Rapist Myth in E.R. Burroughs’ Tarzan of the Apes and Its Film Adaptations - Oklopčić, Biljana (Anafora, 2023)
Whether in art or science, adaptation does not refer to something original but to a mutated and permutated version of a pre-existing original. In literature, adaptation occurs first when real-life stories are adapted into fiction; these fictions then often undergo a second technological adaptation as literary works are adapted into theatrical productions for stage or film. This paper explores one such doubled adaptation; it examines how the black rapist myth, which grew out of the social and cultural realities of the Jim Crow South, was transformed in E.R. Burroughs’ portrayal of Terkoz in the popular adventure novel, Tarzan of the Apes (1914), and then how this fiction was adapted into multiple and varied films between 1918 and 2016.